The fast and the furious [videorecording (DVD)] - Cohen, Rob, 1949-; Diesel, Vin; Walker, Paul, 1973-2013; Rodriguez, Michelle; Brewster, Jordana, 1980-; Ortiz, John; Alonso, Laz; Thompson, Gary Scott (Universal, 2001)
Every night is a championship race on the turbo-charged streets of Los Angeles. Dominic and Johnny are rivals who are the boldest, the baddest, the best, and turn their challengers into dust. Along comes a challenger. Dominic and Johnny know that he is tough and fast, what they don't know is that he is a speed demon detective trying to bust up a theft ring.